Infanticide in Tudor and Stuart England - Billingham, Josephine (Amsterdam : Amsterdam University Press, 2019)
Infanticide in Tudor and Stuart England explores one of society's darkest crimes using archival sources and discussing its representation in the drama, pamphlets and broadside ballads of the early modern period. It takes the reader on a journey through the streets and taverns where street literature was hawked, to the playhouses where the crime was dramatized, and the courts where it was tried and punished. Using a regional microstudy of coroners' inquests and churchwardens' presentments, coupled with theories of liminality, marginality and rites of passage, it reveals complex and contradictory attitudes to infants, women and the crime. As well as considering unwed women, the most common perpetrators of infanticide, the study shows that married women, men and the local community were also culpable, and the many reasons for this. Infanticide in Tudor and Stuart England is set in its European and historical contexts, revealing surprising continuities across time.
Frontmatter -- Contents -- Acknowledgments -- Author's notes -- 1. Losses, Lacunae and Liminality -- 2. European and Medieval Contexts of Infanticide -- 3. The Liminal Child and Mother -- 4. Love, Law and Liminality -- 5. Constructing Outsiders, Constructing Killers -- 6. Not the Usual Suspects: Communities and Accomplices -- 7. Not the Usual Suspects: Married Women -- 8. Not the Usual Suspects: Men -- 9. Interlude: Infanticide 1700-1950 -- 10. Epilogue: Echoes of the Past -- Appendix 1. The 1624 Infanticide Act -- Appendix 2. Note on Sussex Coroners' inquests -- Appendix 3. Sussex Cases of Violent, Unnatural, Unexplained Infant Death 1547-1686 -- Appendix 4. Sussex Infant Deaths Involving Water -- Appendix 5. Sussex Infant Deaths Involving Throwing -- Appendix 6. Sussex Infant Deaths Involving Bloodshed or Extreme Violence -- Appendix 7 Sussex Infant Deaths Showing Direct Involvement of Men -- Index
Print version record.
Includes bibliographical references and index.
JSTOR
Keywords: Infanticide -- England -- History; Infanticide in literature; Infanticide -- Angleterre -- Histoire; Infanticide dans la littérature.; Literary studies: c. 1500 to c. 1800.; Early modern history: c 1450/1500 to c 1700.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Infanticide; England; Infanticide, liminality, pregnancy, childbirth, punishment; History